Preparation method of non-silicon emulsion defoaming agent

The non-silicon emulsion defoaming agent is prepared by D-phase emulsion method, and combined with high-grade fatty alcohols, paraffin, surfactants and polyols, the stability and foam suppression properties of existing non-silicon defoaming agents during storage are solved. , achieving good stability and foam-repelling performance of the emulsion, and enhancing the market advantages of the product.

CN119215490APending Publication Date: 2024-12-31JIANGSU SIXIN SCI-TECH APPL RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310780277.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing non-silicon defoaming agents are prone to poor emulsion phase separation, thickening or foam suppression performance when stored, which affects their market advantages and industrial applications.

Method used

Non-silicon emulsion defoaming agent is prepared by D-phase emulsion method, by mixing high-grade fatty alcohols, paraffin, surfactants, polyols, anionic surfactants and thickeners in a specific proportion, and slowly adding the aqueous phase under stirring conditions , further emulsification through high-speed shearing equipment, increasing the stability of the emulsion and foam-repelling performance.

Benefits of technology

The good stability and foam-repelling performance of the emulsion are achieved, and the large viscosity changes and paste formation during the storage process are avoided, thereby improving the storage and application efficiency of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

A stable emulsion is prepared by adopting a D-phase emulsification method, firstly, an emulsifier A and an emulsifier B are mixed to form a compound emulsifier, the compound emulsifier is further uniformly mixed with polyhydric alcohol, then an oil phase is slowly added into the system under the stirring condition, and a water phase is continuously added to obtain the emulsion; finally, the stability of the emulsion is further improved by the added anionic surfactant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a non-silicon emulsion defoamer. The defoamer is a fine chemical additive, so the invention belongs to the technical field of fine chemicals. Background Art

[0002] According to the key active components of defoaming, defoamers can be mainly divided into silicone defoamers and non-silicone defoamers. Silicone defoamers have the characteristics of small addition amount, low surface tension, no physiological activity, and high safety. However, in some cases, low surface tension and good spreading performance have become the disadvantages of silicone defoamers. This is because once the silicone demulsifies, it is easy to form silicon spots on the surface or cause pump blockage, which has an adverse effect on industrial production. Non-silicone defoamers mainly include polyether defoamers, mineral oil defoamers and fatty alcohol defoamers. Compared with silicone defoamers, non-silicone defoamers have excellent compatibility with industrial additives and do not affect the stability of the foaming system. Among them, fatty alcohol defoamers not only have good compatibility, but also have good degassing properties, which can eliminate fine bubbles in the application system. They have good application performance in some special industries, such as papermaking and papermaking. This is because the foaming white water in the process of papermaking and papermaking contains many fine fibers and fillers. Fatty alcohol defoamers can not only eliminate surface foam, but also remove fine bubbles in fibers and fillers, avoiding spots, light spots and small holes on the paper surface, thereby improving production efficiency.

[0003] Domestic and foreign researchers have conducted a lot of research on fatty alcohol emulsion defoamers, mainly focusing on stability and foam suppression performance. CN106075961A introduces a water-soluble homopolymer-stabilized fatty alcohol emulsion defoamer and a preparation method thereof, which adopts the method of adding a water-soluble homopolymer to reduce the emulsion phase separation and inhibit gelation and viscosity increase. The emulsion phase separation, gel block generation and thickening phenomenon of fatty alcohol emulsion during storage are solved. However, the foam suppression performance of this product is poor and does not have a good market advantage. CN107059474A introduces a high-carbon alcohol defoamer, which is composed of rice bran wax, wax, alkane or vegetable oil, surfactant, bactericide, and water, wherein rice bran wax is the active ingredient of the defoamer. Rice bran wax has a large amount of hexacosanol, octacosanol, triacontanol and corresponding alcohol esters, and has a good foam suppression effect. However, the composition of this product is too complex, the emulsification process is required to be high, and the viscosity changes greatly, and it is easy to form a paste; CN109432830A introduces a preparation method of a high-carbon alcohol-based high-temperature defoamer, which uses high-carbon alcohol, mineral oil, fatty alcohol polyether polyol, and polyether-modified silicone oil as emulsified substances to obtain emulsion A, and emulsion B made of microcrystalline wax is compounded, and stirred at above 180°C to obtain the final emulsion. The emulsification method adopts a method of mixing active substances and emulsifiers separately to make the emulsification more complete, but the emulsion product has a large viscosity, poor dispersibility, and is easy to form a paste; CN107137959B prepares separately emulsified fatty alcohol emulsions, oil emulsions, and paraffin emulsions, and finally the three emulsions are compounded to form a final emulsion to improve the stability of the emulsion, but the three emulsions need to be prepared separately during the preparation of the product, and the process is relatively cumbersome. In CN11790183A, paraffin, fatty alcohol, fatty acid ester, white carbon black, etc. are melted and stirred as the oil phase, and then hot water is added and stirred and then emulsified by colloid mill to obtain a fatty alcohol emulsion. White carbon black is added to the emulsion, which improves the stability of the emulsion, but the addition of white carbon black affects the compatibility of the defoamer. In the preparation process of the fatty alcohol emulsion, CN104707368A forms a stable emulsion system under the synergistic effect of hydrophilic and lipophilic surfactants, Guerbet alcohol, biopolysaccharide alcohol and viscosity control agent, but the introduction of Guerbet alcohol and biopolysaccharide alcohol leads to an increase in cost. . Summary of the invention

[0004] The present invention adopts a D-phase emulsification method to prepare a stable emulsion. First, emulsifier A and emulsifier B are mixed to form a composite emulsifier, which is further mixed evenly with a polyol. Then, an oil phase is slowly added to the system under stirring conditions, and an aqueous phase is continuously added to obtain an emulsion. Finally, an anionic surfactant is added to further improve the stability of the emulsion.

[0005] Technical Solution The preparation method of a non-silicon emulsion defoamer described in the present invention is composed of the following components: A. Higher fatty alcohol The fatty alcohol is a C12-C30 fatty alcohol, selected from one or a mixture of synthetic fatty alcohols and natural fatty alcohols; specifically selected from C12 alcohol, C14 alcohol, C16 alcohol, C18 alcohol, C20 alcohol, C22 alcohol, C24 alcohol, C26 alcohol, C28 alcohol, C30 alcohol; and mixed fatty alcohols containing different numbers of carbon atoms, such as C12-18 mixed alcohol, C16-18 mixed alcohol, C16-22 mixed alcohol, one or more of which are selected. The amount of fatty alcohol used accounts for 15-25% of the total mass of the defoamer.

[0006] B. Paraffin The paraffin is selected from microcrystalline paraffin and liquid paraffin. The amount of paraffin accounts for 2-8% of the total mass of the defoamer.

[0007] C. Surfactant 1 The surfactant 1 described in the present invention is a higher fatty alcohol fatty acid ester, which is obtained by ester exchange reaction of C20-C30 fatty alcohol and C2-C10 fatty acid ester; the amount of the higher fatty alcohol fatty acid ester accounts for 3-5% of the total mass of the defoamer.

[0008] D. Surfactant 2 The surfactant 2 is a fatty alcohol polyoxyethylene ether, and the general structural formula is RO(EO) m H, wherein R is a 5-10 alkyl group, and m is an integer of 10-40; the amount of surfactant 2 is 0.5-3% of the total mass of the defoamer.

[0009] E. Polyol The polyol is selected from one or more of propylene glycol, glycerol, and ethylene glycol, and its usage accounts for 0.5-3% of the total mass of the defoamer.

[0010] F. Anionic surfactant The anionic surfactant is selected from one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl phosphate, sodium dodecyl diphenyl ether disulfonate, and the amount of the anionic surfactant is 0.03-0.1% of the total mass of the defoamer.

[0011] G. Thickener The thickener is selected from one or more of xanthan gum, guar gum, xanthan gum, hydroxymethyl cellulose, hydroxyethyl cellulose, methyl cellulose, polyacrylic acid, and polyacrylamide. The thickener is preferably polyacrylic acid. The amount of the thickener accounts for 0.02% to 0.1% of the total mass of the defoamer.

[0012] H. Water The water described in the present invention is deionized water, and its usage accounts for 60-75% of the total mass of the defoamer.

[0013] The preparation method of the non-silicon emulsion defoamer described in the present invention is as follows: (1) Mix and stir prescribed amounts of surfactant 1, surfactant 2, and polyol to form a mixture M; (2) Mix the specified amount of higher fatty alcohol and paraffin, heat to 70-100°C, stir and mix evenly, keep the temperature constant, slowly add the mixture M, and stir to mix evenly; (3) Cooling to room temperature, adding anionic surfactant, stirring and mixing evenly, slowly adding water to the above mixture, and then further emulsifying through a high-speed shearing device; (4) Finally, add the thickener and adjust to the desired viscosity. DETAILED DESCRIPTION Example 1

[0015] (1) 5 g surfactant 1 (obtained by transesterification of 20-carbon fatty alcohol and methyl acetate), 3 g C5H 11 O(EO) 35 H and 2 g of propylene glycol were mixed and stirred to form a mixture M1; (2) Mix 15g of C12-C18 mixed fatty alcohol and 8g of microcrystalline wax and heat to 70-100°C, stir and mix evenly, keep the temperature constant, slowly add mixture M1, and stir to mix evenly; (3) Cool to room temperature, add 0.1 g of sodium dodecyl sulfate, stir and mix evenly, slowly add 66.8 g of water to the above mixture, and then further emulsify it through a high-speed shearing device; (4) Finally, add 0.1 g of a mixture of xanthan gum and guar gum as a thickener and adjust the mixture to the desired viscosity.

[0016] Example 2 (1) 3 g of surfactant 1 (obtained by transesterification of 2-carbon fatty alcohol with methyl valerate) and 1 g of C6H 13 O(EO) 25 H and 2 g of propylene glycol were mixed and stirred to form a mixture M2; (2) Mix 20g of C16-C18 mixed fatty alcohol and 6g of liquid paraffin and heat to 70-100°C, stir and mix evenly, keep the temperature constant, slowly add mixture M2, and stir to mix evenly; (3) Cool to room temperature, add 0.05 g of sodium dodecylbenzene sulfonate, stir and mix evenly, slowly add 67.9 g of water to the above mixture, and then further emulsify it through a high-speed shearing device; (4) Finally, add 0.05 g of xanthan gum thickener and adjust to the desired viscosity.

[0017] Example 3 (1) 4 g of surfactant 1 (obtained by transesterification of 25-carbon fatty alcohol with methyl octanoate), 0.5 g of C7H 15 O(EO) 10 H and 0.5 g of ethylene glycol were mixed and stirred to form a mixture M3; (2) Mix 25g of C16-C22 mixed fatty alcohol and 2g of microcrystalline wax and heat to 70-100°C, stir and mix evenly, keep the temperature constant, slowly add mixture M3, and stir to mix evenly; (3) Cool to room temperature, add 0.03 g of sodium dodecyl phosphate, stir and mix evenly, slowly add 67.95 g of water to the mixture, and then further emulsify it through a high-speed shearing device; (4) Finally, add 0.02 g of a mixture of hydroxymethyl cellulose and hydroxyethyl cellulose as a thickener and adjust the viscosity to the desired level.

[0018] Example 4 (1) 5 g of surfactant 1 (obtained by transesterification of octadecyl alcohol and methyl decanoate), 1.8 g of C8H 17 O(EO) 15 H, 3g of propylene glycol and ethylene glycol mixture were mixed and stirred uniformly to form a mixture M4; (2) Mix 24g of C22 alcohol and 6g of liquid paraffin and heat to 70-100°C, stir and mix evenly, keep the temperature constant, slowly add mixture M4, and stir to mix evenly; (3) Cool to room temperature, add 0.1 g of sodium dodecyl diphenyl ether disulfonate, stir and mix evenly, slowly add 60 g of water to the above mixture, and then further emulsify it through a high-speed shearing device; (4) Finally, add 0.1 g of methyl cellulose thickener and adjust to the desired viscosity.

[0019] Example 5 (1) 3 g of surfactant 1 (obtained by transesterification of 30-carbon fatty alcohol with methyl propionate), 1 g of C9H 19 O(EO) 40 H, 0.8 g of propylene glycol and glycerol mixture were mixed and stirred to form a mixture M5; (2) Mix 22.13 g of a mixture of C12 alcohol and C14 alcohol and 3 g of microcrystalline wax and heat to 70-100°C, stir and mix evenly, keep the temperature constant, slowly add the mixture M5, and stir to mix evenly; (3) Cool to room temperature, add 0.04 g of a mixture of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate, stir and mix evenly, slowly add 70 g of water to the mixture, and then further emulsify it through a high-speed shearing device; (4) Finally, add 0.03 g of a mixture of polyacrylic acid and polyacrylamide as a thickener and adjust the viscosity to the desired level.

[0020] Example 6 (1) 3 g of surfactant 1 (obtained by transesterification of 2-carbon fatty alcohol and methyl butyrate), 0.5 g of C 10 H 21 O(EO) 20 H, 0.5 g of propylene glycol and ethylene glycol mixture were mixed and stirred to form a mixture M6; (2) Mix 18.95 g of a mixture of C28 alcohol and C30 alcohol and 2 g of microcrystalline wax and heat to 70-100°C, stir and mix evenly, keep the temperature constant, slowly add the mixture M6, and stir to mix evenly; (3) Cooling to room temperature, adding 0.03 g of a mixture of sodium dodecyl phosphate and sodium dodecyl diphenyl ether disulfonate, stirring and mixing evenly, slowly adding 75 g of water to the above mixture, and then further emulsifying it through a high-speed shearing device; (4) Finally, add 0.02 g of polyacrylic acid thickener and adjust to the desired viscosity.

[0021] Comparative Example 1 (1) 5 g of surfactant 1 (obtained by transesterification of 20-carbon fatty alcohol and methyl acetate), 5 g of C5H 11 O(EO) 35 H mixed and stirred evenly to form a mixture M7; (2) Mix 15g of C12-C18 mixed fatty alcohol and 8g of microcrystalline wax and heat to 70-100°C, stir and mix evenly, keep the temperature constant, slowly add mixture M7, and stir to mix evenly; (3) Cool to room temperature, add 0.1 g of sodium dodecyl sulfate, stir and mix evenly, slowly add 66.8 g of water to the above mixture, and then further emulsify it through a high-speed shearing device; (4) Finally, add 0.1 g of a mixture of xanthan gum and guar gum as a thickener and adjust the mixture to the desired viscosity.

[0022] Comparative Example 2 (1) 4gC6H 13 O(EO) 25 H, 2g of propylene glycol were mixed and stirred evenly to form a mixture M8; (2) Mix 20g of C16-C18 mixed fatty alcohol and 6g of liquid paraffin and heat to 70-100°C, stir and mix evenly, keep the temperature constant, slowly add mixture M8, and stir to mix evenly; (3) Cool to room temperature, add 0.05 g of sodium dodecylbenzene sulfonate, stir and mix evenly, slowly add 67.9 g of water to the above mixture, and then further emulsify it through a high-speed shearing device; (4) Finally, add 0.05 g of xanthan gum thickener and adjust to the desired viscosity.

[0023] Comparative Example 3 (1) 4.5 g of surfactant 1 (obtained by transesterification of 25-carbon fatty alcohol and methyl octanoate) and 0.5 g of ethylene glycol were mixed and stirred to form a mixture M9; (2) Mix 25g of C16-C22 mixed fatty alcohol and 2g of microcrystalline wax and heat to 70-100°C, stir and mix evenly, keep the temperature constant, slowly add mixture M9, and stir to mix evenly; (3) Cool to room temperature, add 0.03 g of sodium dodecyl phosphate, stir and mix evenly, slowly add 67.95 g of water to the mixture, and then further emulsify it through a high-speed shearing device; (4) Finally, add 0.02 g of a mixture of hydroxymethyl cellulose and hydroxyethyl cellulose as a thickener and adjust the viscosity to the desired level.

[0024] Comparative Example 4 (1) 5 g of surfactant 1 (obtained by transesterification of octadecyl alcohol and methyl decanoate), 1.8 g of C8H 17 O(EO) 15 H, 3g of propylene glycol and ethylene glycol mixture were mixed and stirred uniformly to form a mixture M4; (2) Mix 24g of C22 alcohol and 6g of liquid paraffin and heat to 70-100°C, stir and mix evenly, keep the temperature constant, slowly add mixture M4, and stir to mix evenly; (3) Cooling to room temperature, slowly adding 60.1 g of water to the above mixture, and then further emulsifying it through a high-speed shearing device; (4) Finally, add 0.1 g of methyl cellulose thickener and adjust to the desired viscosity.

[0025] Performance Testing

[0026] 1 Emulsion stability test The emulsions prepared in the above examples and comparative examples were placed at 5°C, 25°C, and 40°C for 6-month viscosity tracking tests. The specific viscosity test method uses a NDJ-8 digital display viscometer, 2# rotor, and 6rpm conditions for testing. The specific situation is shown in Table 1 below (viscosity unit mPa.s, "-" means the emulsion is a paste and cannot flow): Table 1 Changes in emulsion viscosity at different storage temperatures

[0027] From the viscosity tracking data, it can be seen that the viscosity of the defoamer prepared by the present invention changes slightly when stored at 5°C, 25°C and 40°C for 6 months, showing good storage stability. The viscosity of the fatty alcohol emulsions prepared in Comparative Examples 1-4 increases to varying degrees after 6 months.

[0028] 2. Test method for anti-foaming performance:

[0029] The performance of the defoaming agent is determined by the circulating bubbling method. Add 600 ml of white water into the circulating bubbling equipment and heat it to the required temperature. Turn on the flow pump and circulate at a flow rate of 8 / L min until the foam volume reaches 300 ml. Add 6 ul of defoaming agent and record the change of foam volume over time. Within the same time, the smaller the volume, the better the defoaming and antifoaming performance; the longer the time for the foam to reach 300 ml again, the better the antifoaming performance.

[0030]

[0031]

[0032] The fatty alcohol emulsion prepared by the invention exhibits good foam elimination and suppression performance at 30°C and 55°C.

Claims

1. A method for preparing a non-silicon emulsion defoamer, comprising the following components: A. Higher fatty alcohol The fatty alcohol is a C12-C30 fatty alcohol, selected from one or a mixture of synthetic fatty alcohols and natural fatty alcohols; specifically selected from C12 alcohol, C14 alcohol, C16 alcohol, C18 alcohol, C20 alcohol, C22 alcohol, C24 alcohol, C26 alcohol, C28 alcohol, C30 alcohol; and mixed fatty alcohols containing different numbers of carbon atoms, such as C12-18 mixed alcohol, C16-18 mixed alcohol, C16-22 mixed alcohol, one or more of which are selected; the amount of the fatty alcohol accounts for 15-25% of the total mass of the defoamer; B. Paraffin The paraffin is selected from microcrystalline paraffin and liquid paraffin; the amount of paraffin accounts for 2-8% of the total mass of the defoamer; C. Surfactant 1 The surfactant 1 is a higher fatty alcohol fatty acid ester, which is obtained by transesterification of C20-C30 fatty alcohol and C2-C10 fatty acid ester; the amount of the higher fatty alcohol fatty acid ester accounts for 3-5% of the total mass of the defoamer; D. Surfactant 2 The surfactant 2 is a fatty alcohol polyoxyethylene ether, and the general structural formula is RO(EO)mH, wherein R is a 5-10 alkyl group, and m is an integer of 10-40; the amount of the surfactant 2 accounts for 0.5-3% of the total mass of the defoamer; E. Polyols The polyol is selected from one or more of propylene glycol, glycerol, and ethylene glycol, and the amount used accounts for 0.5-3% of the total mass of the defoamer; F. Anionic surfactant The anionic surfactant is selected from one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl phosphate, and sodium dodecyl diphenyl ether disulfonate; the amount of the anionic surfactant accounts for 0.03 to 0.1% of the total mass of the defoamer; G. Thickener The thickener is selected from one or more of xanthan gum, guar gum, xanthan gum, hydroxymethyl cellulose, hydroxyethyl cellulose, methyl cellulose, polyacrylic acid, and polyacrylamide, and the amount of the thickener accounts for 0.02% to 0.1% of the total mass of the defoamer; H. Water The water is deionized water, and its usage accounts for 60-75% of the total mass of the defoamer.

2. The method for preparing a non-silicon emulsion defoamer according to claim 1, characterized in that: The preparation method of the non-silicon emulsion defoamer is as follows: (1) Mix and stir prescribed amounts of surfactant 1, surfactant 2, and polyol to form a mixture M; (2) Mix the specified amount of higher fatty alcohol and paraffin, heat to 70-100°C, stir and mix evenly, keep the temperature constant, slowly add the mixture M, and stir to mix evenly; (3) Cooling to room temperature, adding anionic surfactant, stirring and mixing evenly, slowly adding water to the above mixture, and then further emulsifying through a high-speed shearing device; (4) Finally, add the thickener and adjust to the desired viscosity.

3. The method for preparing a non-silicon emulsion defoamer according to claim 1, characterized in that: The thickener is polyacrylic acid.